Utilization of Various Wastes in Maggot Cultivation AsLivestock Feed in Kamang Magek District, Agam Regency: Pemanfaatan Berbagai Limbah pada Budidaya Maggot Sebagai Pakan Ternak Di Kecamatan Kamang Magek Kabupaten Agam - Hera Dwi Triani; Rini Suryanti; Dina Ediani; Iratna Dewi; Nandie Hayati; Junios; Gusri Yanti; Desi Ratna Sari; Reni Elmiati; Yurma Metri; Resolinda Harly; Dona Kurnia (Journal of Community Service and Application of Science, 2023)
Kamang Magek District is one of the sub-districts located in the eastern part of Agam Regency. Many small and medium enterprises (SMEs) are developing in Kamang Magek District, several UKM and farmer groups produce various by-products of organic waste which often become environmental problems. In addition to MSME waste, there is also household waste and market waste which often cause environmental pollution. These wastes can be used as feed for maggot development. Maggot cultivation apart from being a solution to environmental pollution is also a good source of protein for poultry feed which can increase livestock productivity. The community problems encountered in Kamang Magek District are the large amount of organic waste that pollutes the environment, the low productivity of livestock and the income of farmer groups. Community service is carried out through lectures, discussions, socialization of science and technology and demonstrations of how and how to apply maggot as animal feed. The Community Service was held in the BPP Hall of Kamang Magek District attended by 15 duck breeders, chicken breeders and catfish breeders selected by BPP Kamang Magek District. Based on the discussion results, more than 75% of breeders only provide feed in the form of rice bran and household waste residue and only 15% of breeders provide feed in the form of self-formulated feed using corn, bran and concentrate purchased at the poultry shop and 10% of breeders provide concentrate feed that has become the result of a feed factory formulation. Of all the breeders, there are no breeders who use maggot as feed for their livestock, this is because there are no breeders who have succeeded in cultivating maggot even though they have tried several times but failed. Based on the results of discussions with participants, breeders are interested in developing maggot cultivation because of the large amount of waste used as maggot feed as a cost-efficient solution for duck or chicken feed.